2018
DOI: 10.1177/0954406218781910
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PA66 nanofiber yarn on tensile fracture toughness of reinforced epoxy nanocomposite

Abstract: Epoxy resin as a thermoset polymer is frequently used in engineering applications. Its nature as a thermoset resin results in brittleness of material structure, which ultimately leads to low toughness; so its modification with thermoplastic polymers is of prime interest. This work aims at studying of tensile properties and morphological characterization of Polyamide 66 (PA66) nanofiber yarn reinforced epoxy nanocomposite. Decrease in elastic modulus and enhancement in tensile toughness were achieved by increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Through the adjustment in the ratio of the rotary speed of metallic funnel to the translational speed of the core yarns in the assembly, twist per meter (TPM) is defined according to the winding speed, rotating speed and roller diameter, and thus serves as a critical parameter associated with yarn production and yarn structure. [21][22][23][24][25][26][27] Therefore, we refer to the definition of TPM to measure the preparation of nanofiber-wrapped yarns of various specifications. Since the yarn keeps the same thickness of 200 D, the definition of TPM based on our experimental setting is as follows:…”
Section: Preparation Of Piezoelectric Wrapped Yarnsmentioning
confidence: 99%
“…Through the adjustment in the ratio of the rotary speed of metallic funnel to the translational speed of the core yarns in the assembly, twist per meter (TPM) is defined according to the winding speed, rotating speed and roller diameter, and thus serves as a critical parameter associated with yarn production and yarn structure. [21][22][23][24][25][26][27] Therefore, we refer to the definition of TPM to measure the preparation of nanofiber-wrapped yarns of various specifications. Since the yarn keeps the same thickness of 200 D, the definition of TPM based on our experimental setting is as follows:…”
Section: Preparation Of Piezoelectric Wrapped Yarnsmentioning
confidence: 99%
“…Among these synthetic polymers, nylon 66 (polyamide 66, PA66) is a multifunctional synthetic thermoplastic polymer broadly used in textiles, parachutes, biomedical fields, and functional materials [25]. It was reported that PA66 has been successfully used to modify epoxy resins to achieve tensile toughness enhancement [26], however there has been limited work related to the use of PA66 for the modification of natural polymers, especially gelatin. Owing to its anti-abrasion resistance, high mechanical strength, light weight, relatively low cost and, very importantly, biological safety [27][28][29][30][31], PA66 can be used as a potential modification material for gelatin.…”
Section: Introductionmentioning
confidence: 99%
“…Using thermoplastics as additives in thermoset-based CFRPs is an attractive method for enhancing their fracture toughness [11][12][13][14]. These additives can be in the form of particles [15][16][17][18], film [19,20], or fibers [21][22][23][24][25][26], and range in size from nano-to micrometers. These types of materials have long been used for toughening laminates, except for nanofibers which were introduced in the last few years [27] and have not attracted researchers' attention until recently [28].…”
Section: Introductionmentioning
confidence: 99%